PERAN ORANG TUA DALAM MEMBINA IBADAH SHALAT ANAK DI DESA HAYURAJA KECAMATAN PANYABUNGAN SELATAN KABUPATEN MANDAILING NATAL - Nurul Husna (Yayasan Baitul Hikmah al-Zain, 2025)
Children in Hayuraja Village, Panyabungan Selatan District, Mandailing Natal Regency, still leave many of their prayers at dawn and midday. This devotional problem is to find out the role of parents in fostering children's prayer worship in Hayuraja Village, Panyabungan Selatan District, Mandailing Natal Regency, and also to find out what are the inhibiting and supporting factors in fostering children's prayer worship in fostering children's prayer worship in Hayuraja Village, Panyabungan Selatan District, Mandailing Natal Regency. The devotional method is carried out by mentoring/counseling to parents and their children. The results of the study are in Hayuraja Village, the role of parents in fostering children's prayer worship is still less than optimal, especially in children's prayers at dawn and midday. This is caused by the busyness of parents so they pay less attention and, and also caused by technological advances that cause children to be addicted to playing with cellphones and cause children to often stay up late so they fall asleep at dawn and leave the dawn prayer. Parents overcome this by giving encouragement to children and also giving special attention to children.